Avoiding New Biopsies by Identification of IDH1 and TERT Promoter Mutation in Nondiagnostic Biopsies From Glioma Patients - Barritault, Marc; Picart, Thiébaud; Poncet, Delphine; Fenouil, Tanguy; d’Hombres, Anne; Gabut, Mathieu; Guyotat, Jacques; Jouanneau, Emmanuel; Ameli, Roxana; Joubert, Bastien; Streichenberger, Nathalie; Vasiljevic, Alexandre; et al. (Neurosurgery, 2020)
Abstract BACKGROUND Biopsies in patients with a suspected glioma are occasionally nondiagnostic. OBJECTIVE To explore the utility of molecular testing in this setting by determining whether IDH1 and TERT promoter (pTERT) mutations could be detected in nondiagnostic biopsies from glioma patients. METHODS Using SNaPshot polymerase chain reaction, we retrospectively assessed IDH1 and pTERT mutation status in nondiagnostic biopsies from 28 glioma patients. RESULTS The nondiagnostic biopsy (needle biopsy n = 25, open or endoscopic biopsy n = 3) consisted of slight glial cell hypercellularity, hemorrhage, and/or necrosis. After another biopsy (n = 23) or a subsequent surgical resection (n = 5) the diagnosis was an IDH1-wildtype (WT) pTERT-mutant glioma (glioblastoma n = 16, astrocytoma n = 4), an IDH1-mutant pTERT-mutant oligodendroglioma (n = 1), an IDH1-mutant pTERT-WT astrocytoma (n = 1), and an IDH1-WT pTERT-WT glioblastoma (n = 6). An IDH1 mutation was identified in the nondiagnostic biopsies of the 2 IDH-mutant gliomas, and a pTERT mutation in the nondiagnostic biopsies of 16 out of the 21 of pTERT mutant-gliomas (76%). Overall, an IDH1 and/or a pTERT mutation were detected in 17 out of 28 (61%) of nondiagnostic biopsies. Retrospective analysis of the nondiagnostic biopsies based on these results and on imaging characteristics suggested that a new biopsy could have been avoided in 6 patients in whom a diagnosis of “molecular glioblastoma” could have been done with a high level of confidence. CONCLUSION In the present series, IDH1 and pTERT mutations could be detected in a high proportion of nondiagnostic biopsies from glioma patients. Molecular testing may facilitate the interpretation of nondiagnostic biopsies in patients with a suspected glioma.